Increased Excitability of Afferent Neurons Innervating Rat Urinary Bladder after Chronic Bladder Inflammation - Yoshimura, Naoki (J Neurosci, 1999)
The properties of bladder afferent neurons in L(6) and S(1) dorsal root ganglia of adult rats were evaluated after chronic bladder inflammation induced by 2 week treatment with cyclophosphamide (CYP; 75 mg/kg). Whole-cell patch-clamp recordings revealed that most (70%) of the dissociated bladder afferent neurons from control rats were capsaicin sensitive, with high-threshold long-duration action potentials that were not blocked by tetrodotoxin (TTX; 1 μm). These neurons exhibited membrane potential relaxations during voltage responses elicited by depolarizing current pulses and phasic firing during sustained membrane depolarization. After CYP treatment, a similar proportion (71%) of bladder afferent neurons were capsaicin sensitive with TTX-resistant spikes. However, the neurons were significantly larger in size (diameter 29.6 ± 1.0 μm vs 23.6 ± 0.8 μm in controls). TTX-resistant bladder afferent neurons from CYP-treated rats exhibited lower thresholds for spike activation (−25.4 ± 0.5 mV) than those from control rats (−21.4 ± 0.9 mV) and did not exhibit membrane potential relaxation during depolarization. Seventy percent of TTX-resistant bladder afferent neurons from CYP-treated rats exhibited tonic firing (average 12.3 ± 1.4 spikes during a 500 msec depolarizing pulse) versus phasic firing (1.2 ± 0.2 spikes) in normal bladder afferent neurons. Application of 4-aminopyridine (1 mm) to normal TTX-resistant bladder afferent neurons mimicked the changes in firing properties after CYP treatment. The peak density of an A-type K(+) current (I(A)) during depolarizations to 0 mV in TTX-resistant bladder afferent neurons from CYP-treated rats was significantly smaller (42.9 pA/pF) than that from control rats (109.4 pA/pF), and the inactivation curve of the I(A) current was displaced to more hyperpolarized levels by ∼15 mV after CYP treatment. These data suggest that chronic inflammation induces somal hypertrophy and increases the excitability of C-fiber bladder afferent neurons by suppressing I(A) channels. Similar electrical changes in sensory pathways may contribute to cystitis-induced pain and hyperactivity of the bladder.